2020
DOI: 10.1007/s00027-020-0696-2
|View full text |Cite
|
Sign up to set email alerts
|

Responses of lake phytoplankton communities to changing inorganic nitrogen supply forms

Abstract: A shift has been predicted in future nitrogen emission scenarios from nitrous oxide to higher proportions of ammonium compounds. To investigate the interaction between increasing nitrogen load and varying nitrate:ammonium ratios (NO 3 − :NH 4 +), we performed a mesocosm experiment in an oligotrophic lake in southern Germany. We fertilized mesocosms with both roughly natural and four times the natural nitrogen wet deposition amounts in molar NO 3 − :NH 4 + ratios of 4:1 and 1:4. We observed greater phytoplankto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The most abundant chlorophyte was Scenedesmus quadricauda, a small coenobium-forming and ammonium-tolerant species [97][98][99] with higher uptake abilities for ammonium under nitrogen limitation than species of the genus Microcystis and with competitive superiority in the large-pulse, low-frequency nutrient recharging [100], as was present in our study area. With regard to size, small algae can be more competitive than larger species, because they have high surface area to volume ratios, resulting in greater specific uptake and growth under low nutrient concentrations, when even slight NH 4 + additions can be enough to promote the growth of small algae [101]. Secondly, the most dominant species during the summer period was Microcystis spp., with the culmination of dominance (surface bloom) in August, which was connected with the maximum of phytoplankton biomass and number of cells per liter.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant chlorophyte was Scenedesmus quadricauda, a small coenobium-forming and ammonium-tolerant species [97][98][99] with higher uptake abilities for ammonium under nitrogen limitation than species of the genus Microcystis and with competitive superiority in the large-pulse, low-frequency nutrient recharging [100], as was present in our study area. With regard to size, small algae can be more competitive than larger species, because they have high surface area to volume ratios, resulting in greater specific uptake and growth under low nutrient concentrations, when even slight NH 4 + additions can be enough to promote the growth of small algae [101]. Secondly, the most dominant species during the summer period was Microcystis spp., with the culmination of dominance (surface bloom) in August, which was connected with the maximum of phytoplankton biomass and number of cells per liter.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these characteristics and based on the results obtained here (i.e., higher accuracy and lower variation), more accurate data with ALA than with the other probes could be expected, as after sampling, this tool can be run under controlled laboratory conditions. As for ALA, few data are reported in the literature, and most of them are related to its use in research experiments to determine Chl- a content and photosynthetic efficiency, rather than for a comparison among detection methodologies [ 48 , 49 , 50 , 51 , 52 ], whereas a strong correlation between cyanobacterial biomass and ALA Chl- a was found in a Swedish lake [ 53 ]. Nonetheless, a general inconsistency between Chl- a quantification methodologies has been previously discussed [ 54 ], and discrepancies among in vivo fluorescence and extraction procedures have been related to the calibration of the bbe Moldaenke probes that are based on HPLC pigment analysis, by which the separation onto chromatograms of distinct Chl- a allomers occurs, resulting in an apparent lower Chl- a content [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively strong temporal signal, reflected here in the linear effect of year (fixed effect) also suggests that there may be a set of important unmeasured environmental parameters that have not been included in our study, such as more detailed inorganic nutrient fractions that have been shown to explain phytoplankton community properties partly better than only including total concentrations (Ptacnik et al . 2010; Trommer et al . 2020).…”
Section: Discussionmentioning
confidence: 99%